Methods of Technical Implementation of Receivers of Systems for Monitoring The State of Rail Lines for Railways Uzbekistan - Azamat Nematullayevich Sadikov (International Journal on Orange Technologies, 2021)
The issues of improving the system for monitoring the state of rail lines with the transfer of technical means to a modern, more reliable microelectronic base are considered. Using the methods of detecting the disorder of random processes and linear filtering, the algorithm of the detector of signals for monitoring the state of rail lines is implemented. The considered algorithm of the receiver of the system for monitoring the states of the rail line can be practically implemented on a microprocessor-based element base.